Differential Measuring Dual Six-Port Concept and Antenna Design for an Inline Foil Thickness Sensor - Mann, Sebastian; Linz, Sarah; Erhardt, Stefan; Lindner, Stefan; Lurz, Fabian; Maune, Holger; Weigel, Robert; Kölpin, Alexander (German Microwave Conference (GeMiC), 2016)
Sensor elements play an important role in future manufacturing plants. This paper presents a solution for an foil thickness sensor for running production lines. Based on the elaborated Six-Port concept, a differential measuring concept is proposed and discussed. Furthermore, an end-fire antenna design for the addressed application is demonstrated and far field measurement results are shown and compared to simulation. Finally, interference effects between two antennas are experimentally investigated as a function of the relative rotation between two oppositely placed device
elib2cris::1512001600,mann2016a